2014
DOI: 10.1680/gein.14.00027
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance of EPDM geomembrane in El Boquerón reservoir

Abstract: El Boquerón reservoir (Canary Islands, northern hemisphere) is waterproofed with an ethylene-propylene-diene terpolymer (EPDM) geomembrane (GM). To evaluate the durability of EPDM GMs in hydraulic applications, the characteristics of the EPDM GM (resin and additives) installed in the El Boquerón reservoir were followed for over 21 years. The results of this study are presented herein and show that, based on measurements of specimens from the north and south slopes of the reservoir, the orientation of the GM in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…For PVC-P, several cases support this conclusion since more than 50% of the additive was lost but the geomembrane has not yet been removed. Moreover, some PVC-P geomembranes installed in Spain exhibited losses higher than 80%, but they still fulfil their working requirements in the reservoirs (Blanco et al 2013b;Noval et al 2014c). Nonetheless, it is important to stress that these geomembranes are reinforced with a synthetic thread textile.…”
Section: Geomembrane End Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…For PVC-P, several cases support this conclusion since more than 50% of the additive was lost but the geomembrane has not yet been removed. Moreover, some PVC-P geomembranes installed in Spain exhibited losses higher than 80%, but they still fulfil their working requirements in the reservoirs (Blanco et al 2013b;Noval et al 2014c). Nonetheless, it is important to stress that these geomembranes are reinforced with a synthetic thread textile.…”
Section: Geomembrane End Of Lifementioning
confidence: 99%
“…Consequently, high-density polyethylene (HDPE) geomembranes began to be used in some waterproofed reservoirs in Castilla-León and the Canary Islands (Noval et al 2014a(Noval et al , 2014b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these studies concluded by recommending that oxidized bituminous GMs not be left exposed after installation. Noval et al (2015) also recently studied the evolution over 21 years of an ethylene propylene diene terpolymer (EPDM) GM installed in a pond in the Canary Islands. After 21 years, the flow rate remained below 10 À6 m 3 m À2 d À1 .…”
Section: Flow Rates For Geomembranes After On-site Exposurementioning
confidence: 99%
“…Figure 2. Tensile behavior of the samples after UV fluorescent device exposure.Tensile properties were evaluated by Noval et al[37] for an HDPE geomembrane with 1.5 mm of thickness during 20 years of weathering exposure in the San Isidro reservoir in Spain. The resistance and elongation presented the same trend during the time examined.…”
mentioning
confidence: 99%